2018
DOI: 10.1016/j.stem.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hepatic Stellate Cells from Human Pluripotent Stem Cells Enables In Vitro Modeling of Liver Fibrosis

Abstract: The development of complex in vitro hepatic systems and artificial liver devices has been hampered by the lack of reliable sources for relevant cell types, such as hepatic stellate cells (HSCs). Here we report efficient differentiation of human pluripotent stem cells into HSC-like cells (iPSC-HSCs). iPSC-HSCs closely resemble primary human HSCs at the transcriptional, cellular, and functional levels and possess a gene expression profile intermediate between that of quiescent and activated HSCs. Functional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
228
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(236 citation statements)
references
References 52 publications
6
228
1
1
Order By: Relevance
“…Importantly, hPSC‐derived HSCs also expressed lecithin‐retinol acyltransferase ( LRAT ) (Fig. ), an enzyme that plays a key role in the formation of retinyl esters for vitamin A storage . This finding further confirmed that the final progeny are HSCs, which differ from fibroblasts in that the latter do not store vitamin A in lipid droplet.…”
Section: Liver Organoid Damage and Fibrosismentioning
confidence: 64%
See 4 more Smart Citations
“…Importantly, hPSC‐derived HSCs also expressed lecithin‐retinol acyltransferase ( LRAT ) (Fig. ), an enzyme that plays a key role in the formation of retinyl esters for vitamin A storage . This finding further confirmed that the final progeny are HSCs, which differ from fibroblasts in that the latter do not store vitamin A in lipid droplet.…”
Section: Liver Organoid Damage and Fibrosismentioning
confidence: 64%
“…HSCs derived by this method express bona fide HSC markers PDGFRA , PDGFRB , CD73 , Desmin ( DES ), and COL1A1 (Fig. ) . Importantly, hPSC‐derived HSCs also expressed lecithin‐retinol acyltransferase ( LRAT ) (Fig.…”
Section: Liver Organoid Damage and Fibrosismentioning
confidence: 97%
See 3 more Smart Citations